Combination of PI-RADS score and PSAD can improve the diagnostic accuracy of prostate cancer and reduce unnecessary prostate biopsies - Wang, Changming; Yuan, Lei; Shen, Deyun; Zhang, Bin; Wu, Baorui; Zhang, Panrui; Xiao, Jun; Tao, Tao (Frontiers in Oncology, 2022)
Objectives: The purpose of this study was to evaluate the diagnostic accuracy of patients’ clinical variables for prostate cancer (PCa) and provide a strategy to reduce unnecessary biopsies. Patients and Methods: A Chinese cohort consists of 833 consecutive patients who underwent prostate biopsies from January 2018 to April 2022 was collected in this retrospective study. The diagnostic ability for total PCa and clinically significant PCa (csPCa) was evaluated by prostate imaging-reporting and data system (PI-RADS) score and other clinical variables. Univariate and multivariable binary logistic regression analyses were performed for figuring out the independent predictors. Diagnostic accuracy was estimated by plotting receiver-operating characteristic (ROC) curves. Results: Results of univariate and multivariable analysis demonstrated that PI-RADS score (P＜0.001, OR: 5.724, 95%CI: 4.517-7.253)/(P＜0.001, OR: 5.199, 95%CI: 4.039-6.488) and prostate-specific antigen density (PSAD) (P＜0.001, OR: 2.756, 95%CI: 1.560-4.870)/(P＜0.001, OR: 4.726, 95%CI: 2.661-8.396) were independent clinical factors for predicting total PCa/csPCa. The combination of PI-RADS score and PSAD presented with best diagnostic performance for the detection of PCa and csPCa. For the diagnostic criterion of ‘PI-RADS scored ≥ 3 or PSAD ≥ 0.3’, the sensitivity and negative predictive value (NPV) were 94.0%, 93.1% for diagnosis of total PCa and 99.2%, 99.3% for diagnosis of csPCa. The specificity and positive predictive values (PPV) were 96.8%, 92.6% for diagnosis of total PCa and 93.5%, 82.4% for diagnosis of csPCa for the diagnostic criterion ‘PI-RADS score >3 and PSAD ≥ 0.3’. Conclusions: The combination of PI-RADS score and PSAD can implement extraordinary diagnostic performance of prostate cancer. Many patients may safely execute active surveillance or take systematic treatment without prostate biopsies by stratification according to PI-RADS score and value of PSAD.